Role of the (104) MgCl2 lateral cut in ziegler-natta catalysis: a computational investigation - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (Journal of Physical Chemistry C, 2018)
Density functional theory (DFT) has been used for the study of ethylene polymerization in the Ziegler-Natta (ZN) olefin polymerization system for eight different alkoxy group containing titanium catalysts (Cat-A-h), Ti(III)Et(OR)(OR') (where R =-CH3,-Et,-tert-butyl, cyclohexane, R' = CH3,-Et,-tert-butyl, cyclohexane). What is of significance is that the catalysts studied were all considered to be tethered to the (104) MgCl2 surface, which has traditionally been considered a ``dormant'' surface in Z-N catalysis systems, in contrast to the ``more active'' (110) MgCl2 surface. Our calculations indicate that the binding of all the catalysts to the (104) surface is favorable, even after taking entropic effects into account. For purposes of comparison, ethylene polymerization has been investigated for the Cat-C (TiEt(OEt)(2)) and the Cat-H (TiEt(CI)(OC4H8Cl)) (OC4H8Cl = the chlorobutoxy group) cases, for both the (i) (110) and the (ii) (104) MgCl2 surfaces. It has been seen that for both (i) and (ii)-the energy gap between insertion and the termination barriers (Delta X) was nearly the same for both the Cat-C and Cat-H eases, which shows that ethylene polymerization on the (104)MgCl2 surface is likely to be a ptoininent occurrence in Z-N catalysis, when alkoxy groups are bound to the titanium center. Additionally, for the Cat-C and the Cat-H cases, the regio-and stereoselective behavior of the propylene monomer on the titanium species present on the (110) and the (104) MgCl2 surfaces has also been investigated, and the results indicate that the (104) MgCl2 surface is only slightly less effective than the (110. However, the calculations also indicate that for Cat-H the (104) MgCl2 surface significantly improves the molecular weight of polypropylene in comparison to the (110) surface, further showcasing how the (104) surface (ignored until date) might be a major player in ZN catalysis. Given that a major portion of the MgCl2 support is made up of (104) lateral cuts, the current findings are of considerable relevance.